PERANCANGAN BUKU POP UP CERITA DONGENG “CINDERALAS” DENGAN TEKNIK V FOLD SEBAGAI UPAYA MENGENALKAN CERITA RAKYAT UNTUK ANAK –ANAK - Kurniawan, Mohammad Ilham; Budiardjo, Hardman; Hidayat, Wahyu (Jurnal Art Nouveau, 2017)
The design of this book aims to increase the reading interest of children by using the media of pop up books and Cindelaras fairy tales. The story of a fairy tale that began to be left by children who are currently switching on television. Pop up book is one of the efforts to introduce the fairy tales story that began to be abandoned. The research used in this design is a qualitative method that conducts interviews, observations, documentation, and literature to obtain the data used to support the illustration design concept from the Cindelaras fairy tale pop up book. After the data analysis process has been done, then found a design concept is "Joyful". Basically, "Joyful" has the meaning is fun. Joyful meaning is actually the concept of an interactive storybook that will be used as a means to provide moral education to the target audience about the story of the Cindelaras fairy tale.The result of this research is to produce a cindelaras pop up book that can cultivate the curiosity of the target audience to recognize or recall the folklore, especially Cindelaras.Kata kunci: Buku Pop Up, Cerita dongeng, Teknik V - Fold.